ELIMINATION OF UNFAVORABLE CONDITIONS FOR THE DEVELOPMENT OF THE CHEWING MACHINE SYSTEM WITH THE HELP OF MYOHYMNASTIC EXERCISES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
To normalize the functional state of the chewing muscle in combination with orthodontic correction, myohymnastics is actively used. Aim: Evaluation of effectiveness of elimination of adverse conditions of chewing apparatus system development with the help of improved algorithm of myohymnastic exercises. Materials and methods: The study involved 64 patients (34 boys, 30 girls) of the Children's Clinical Dental Clinic No. 2 in Voronezh, aged 10-12 years with a distal bite. A comparative analysis of the detection of imbalance in the tone of the chewing muscles in patients performing myogymnastic exercises according to the author's method (group 1) and using the standard method (group 2) in combination with orthodontic correction, before and after 1 month of treatment was carried out. Results: At the pre-treatment stage, there was no statistically significant difference (p = 0.121) between the groups in terms of the imbalance in the tone of the chewing muscle itself in the patients, which indicates the comparability of the groups in this indicator. After 1 month of treatment, we identified statistically significant differences among patients of groups 1 and 2 (p = 0.012): in patients of group 1, the number of children with an imbalance in tone decreased by 62.5%, and in patients of group 2 – by 34.3%. Conclusion: A higher efficiency of using the author's algorithm of myohymnastic exercises compared to the standard method was revealed.
Keywords: myohymnastic exercises, chewing apparatus, tone imbalance